Investigation of temperature sensitivity and storage stability of polyethylene and calcium carbonate compound modified bituminous binders - Erkus, Yunus; Kok, Baha Vural; Yilmaz, Mehmet (Pamukkale Univ, 2022)
In this study, temperature sensitivity and storage stability of polyethylene and calcium carnonate compound (PEC) modified bitumen were investigated. PEC was used at the rates of 3%, 6%, 9%, 12% and 15% by weight of bitumen. The characteristics of PEC additived binders were confronted with 4% styrene-butadiene-styrene (SBS) additived binder. Penetration, rotational viscometer and softening point experiments were applied to determine the temperature sensitivity of the binders. After the storage process, dynamic shear rheometry and softening point experiments were applied to the binders. Moreover, their performance/cost relations were determined with the help of the approximate costs of the binders. According to the test results; The binder containing 15% PEC stands out with its low temperature sensitivity It has been appeared that there was a important phase separation after storage with an additive content of more than 6% in PEC modified binders. When the performance and costs of the binders are evaluated together, it has been determined that the binder containing 6% PEC has similar performance with 4% SBS modification in terms of temperature sensitivity, storage stability and economy.
Keywords: Polyethylene and calcium carbonate compound; Bitumen; Storage stability; Temperature sensitivity; SBS